Distributed acoustic sensing in geophysics : methods and applications - Li, Yingping; Karrenbach, Martin; Ajo-Franklin, Jonathan (U.S. A John Wiley & Sons, 2021)
"Distributed Acoustic Sensing (DAS) systems are optoelectronic instruments which measure acoustic interactions and distributed strain along the length of a fiber optic sensing cable, thus associated with various applications in geophysics, engineering, hazard mitigation, prevention, safety and security fields. The DAS observation system records the sound and vibration signals along several tens of kilometers of sensing optical fiber with fine spatial resolution of 1-10 meters over a wide frequency range (millihertz to tens kilohertz), thereby providing a flexible large sensing aperture for acquiring high resolution acoustic data in both time and space domains. Geophysical Applications of Distributed Acoustic Sensing (DAS): Principles and Practices focuses on the various geophysical applications in geophysics and principles of DAS measurements. Volume highlights include: An up-to-date state of the art of advanced DAS technologies that engages both academic and industrial communities to share their knowledge and experiences with deploying DAS in novel geophysical methods and applications Demonstrates full spectral DAS geophysical applications in generating large amounts of big DAS data within environmental and shallow surface geophysics fields, such as safe storage of carbon dioxide Describes several DAS applications in exploration geophysics for sustainable energy resources, including DAS applications in oil, gas, geothermal, and mining industries Develops and analyzes suitable 3D/4D DAS data processing methods to deal with the big data for efficient and effective extraction of useful geophysical information, such as, monitor reservoir activity in the deep-water wells, optimize velocity models and improve 3D subsurface images in oil and geothermal fields, and use of DAS tomography output in revealing mining excavation activity Describes a crucial tool, micro-seismic DAS for hydraulic monitoring integrated with temperature and strain measurements to improve subsurface reservoir description Discusses the DAS applications that helps monitor local, regional, and global seismicity, detects fault deformations and large earthquakes, builds earthquake early warning systems using new or existing fiber networks, such as the telecommunications conduits, fiber-networks, long pipelines, and existing "dark" fibers cross ocean and around the world Applications of ambient noise interferometry or tomography to DAS continuous records to image the shear wave velocity structures in the near surface for monitoring time-lapse and spatial variations of Earth's near-surface, such as soil properties, water tables, and the thickness of sediment layers Discusses development of suitable data processing methods to deal with the big data for efficient and effective extraction of useful geophysical information Geophysical Applications of Distributed Acoustic Sensing (DAS): Principles and Practices is a valuable resource for geologists, geophysicists, earthquake seismologists, structural geologists, geoengineers, mining engineers, hydrocarbon geologists, engineers, environmental geologists, and industry experts in hazard risk mitigation, emergency preparedness and disaster management agencies"--
Keywords: Geophysics -- Methodology; Optical fiber detectors; Imaging systems in geophysics